Zur Grabwespenfauna der Insel Hiddensee. Ein Beitrag zur Fauna von Naturschutzgebieten der DDR (Hymenoptera: Sphecidae). - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1972)
The continuation of the revision of the Hymenoptera of the island of Hiddensee with special regard to the wild-life preserves deals with the Sphecidae. Of the 177 species of digger wasps regularly occurring in the GDR, 42 species with 259 individuals were collected on this island. The ecological requirements of these species can be grouped into four forms of biotopes. The most interesting digger wasps live on the extensive sandy stretches of Hiddensee which are rich or poor in vegetation. The following rarities may be mentioned: Crossocerus imitans Kohl, Passaloecus clypealis Faester, Miscophus concolor Dahlbom, Podolonia luffii Saunders.